Anxiolytic-like effects of median raphe nucleus lesion in the elevated T-maze - Andrade, TGCS; Macedo, CEA; Zangrossi, H.; Graeff, F. G. (Elsevier B.V., 2004)
The cell bodies of 5-HT containing neurons that innervate the limbic forebrain are mainly found in the dorsal raphe nucleus and in the median raphe nucleus (MRN). To assess the role of the median raphe nucleus in anxiety, rats bearing either electrolytic or 5-HT-selective neurotoxic lesion of the MRN were tested in the elevated T-maze. This apparatus consists of two opposed open arms perpendicular to one enclosed arm. Two tasks are performed in succession by the same rat in one experimental session, namely inhibitory avoidance of the open arm, taken as a measure of conditioned anxiety and one-way escape from the open arm, considered as a measure of unconditioned fear. The test was performed 7 days after the electrolytic lesion (3 mA, 10 s) or 14 days after the neurotoxic lesion (5,7-DHT, 8 mug/1 mul). The results showed that while the electrolytic lesion impaired both inhibitory avoidance and one-way escape, the neurotoxic lesion impaired only inhibitory avoidance. Therefore, serotonergic pathways originating in the MRN seem to participate in the modulation of conditioned anxiety but not unconditioned fear. Other neurotransmitter systems that either originate in or pass through the MRN may regulate unconditioned fear. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: median raphe nucleus; elevated T-maze; 5-HT; anxiety